PENEGAKAN HUKUM TINDAK PIDANA PEMANFAATAN RUANG KOTA DITINJAU DARI PERSPEKTIF BERLAKUNYA UNDANG-UNDANG NOMOR 26 TAHUN 2007 TENTANG PENATAAN RUANG (Studi Di Wilayah Kota Pontianak) - AHMAD SUGIYANTO,SH A.21211068, Jurnal Mahasiswa S2 Hukum UNTAN (Jurnal NESTOR Magister Hukum, 2013)
ABSTRACTThis thesis discusses the issue of Law Enforcement Crime City Land Use Applicability be reviewed From Perspective of Law Number 26, 2007 on Spatial Planning (Studies in Urban Pontianak City). From the results of research using normative legal research methods and sociological conclusion that: 1. Formulation premise of criminal sanctions under the Act No. 26, 2007 on Spatial Planning refers to the norms sanctioned as the norm enforcement, criminal system, the purpose of punishment and the subject matter of the criminal law, has three main elements, namely: